Secondary Traumatic Stress Among Labor and Delivery Nurses. Issue 1 (January 2021) - Nicholls, Erika M.; Hermann, Robin M.; Giordano, Nicholas A.; Trotta, Rebecca L.
Abstract: Purpose: To describe the prevalence and severity of secondary traumatic stress (STS) among labor and delivery nurses within a Northeastern United States academic health system. Study Design and Methods: Using a cross-sectional, descriptive correlational design, a convenience sample of labor and delivery nurses (288 nurses) were invited to complete Secondary Traumatic Stress Scale (STSS), a 17-item Likert-type instrument, that measures intrusion, avoidance, and the arousal symptoms associated with indirect exposure to traumatic events. Five additional questions about potential consequences of STS were also asked. Results: N = 144 completed the survey (50% response rate). Average STSS score was 33.74 (SD, 11.8), with 35% of respondents meeting symptom severity scores associated with STS. STSS Scores ≥ 38 were significantly correlated with nurses considering leaving their jobs, calling out sick, or requesting an assignment change after witnessing a traumatic birth ( p < 0.001). The majority of respondents (84.7%) reported witnessing a traumatic birth. After witnessing a traumatic birth, respondents used co-workers, family, and friends as sources of support. Clinical Implications: This study offers insight into the frequency and severity of STS among labor and delivery nurses, as well as the potential workforce-related consequences and provides a foundation for future work aimed at developing interventions to prevent or alleviate STS. Abstract : Nurses who care for women during labor and birth often witness traumatic events such as pregnancy loss, a stillborn baby, perineal trauma, difficult operative vaginal birth, a depressed newborn at birth, maternal complications including amniotic fluid embolism, massive postpartum hemorrhage and at times, maternal death. These events can lead to secondary traumatic stress. In this study, labor and birth nurses in one three-hospital system share their experiences with secondary traumatic stress.